European Policies Aiming the Penetration of Distributed Energy Resources in the Energy Market - Borges, Nuno (2021)
This work has been supported by the European Commission H2020 MSCA-RISE-2014: Marie Skłodowska- Curie project DREAM-GO Enabling Demand Response for short and real- time Efficient And Market Based Smart Grid Operation -An intelligent and real-time simulation approach ref 641794.